Smoking Status and Survival Among a National Cohort of Lung and Colorectal Cancer Patients. Issue 4 (17th January 2018) - Japuntich, Sandra J; Kumar, Pallavi; Pendergast, Jane F; Juarez Caballero, Grelda Yazmin; Malin, Jennifer L; Wallace, Robert B; Chrischilles, Elizabeth A; Keating, Nancy L; Park, Elyse R
Abstract: Introduction: The purpose of this study was to explore the association of smoking status and clinically relevant duration of smoking cessation with long-term survival after lung cancer (LC) or colorectal cancer (CRC) diagnosis. We compared survival of patients with LC and CRC who were never-smokers, long-term, medium-term, and short-term quitters, and current smokers around diagnosis. Methods: We studied 5575 patients in Cancer Care Outcomes Research and Surveillance (CanCORS), a national, prospective observational cohort study, who provided smoking status information approximately 5 months after LC or CRC diagnosis. Smoking status was categorized as: never-smoker, quit >5 years prior to diagnosis, quit between 1–5 years prior to diagnosis, quit less than 1 year before diagnosis, and current smoker. We examined the relationship between smoking status around diagnosis with mortality using Cox regression models. Results: Among participants with LC, never-smokers had lower mortality risk compared with current smokers (HR 0.71, 95% CI 0.57 to 0.89). Among participants with CRC, never-smokers had a lower mortality risk as compared to current smokers (HR 0.79, 95% CI 0.64 to 0.99). Conclusions: Among both LC and CRC patients, current smokers at diagnosis have higher mortality than never-smokers. This effect should be further studied in the context of tumor biology. However, smoking cessation around the time of diagnosis did not affect survival in this sample. Implications: The results from our analysis of patients in the CanCORS consortium, a large, geographically diverse cohort, show that both LC and CRC patients who were actively smoking at diagnosis have worse survival as compared to never-smokers. While current smoking is detrimental to survival, cessation upon diagnosis may not mitigate this risk.